Structural Anthropology and Deconstruction of Western illusionist mind - Bourenane, Kheira (Journal of Social Sciences and Humanities, 2021)
One of the delusions that shaped the cultural identity of the West is the superiority of its mind, as it is the last thing the human mind has achieved through its successive stages of development. The origins of this delusion go back to what is historically called the Greek miracle, which means that Greek civilization and especially philosophy and science are a pure product of Greek’s great intelligence, that are not referable to other earlier origins. Thus, since the era of modernity, Western and European thought, in particular, has begun to view itself as the bearer of the message of progress and that the way forward would only be possible if the Western mind believed that it is the only responsible to resume civilization. By presenting the Western mind as the axis which all values are articulated around, it represents in contrast another primitive, brutal late vision. However, contemporary Western thought in its Postmodernism image, has clearly revealed the negative face of Western modernity. Postmodernism declared through its different speeches the collapse of Pivot of Nationalism, theory of Deconstruction where the basis of this pretension was deconstructed. It also showed the decline of its premises and acknowledged that the ideological component, not the scientific motivation, was the origin of this statement